Un modèle de dépenses provinciales - Swan, Neil (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThe paper develops a formal theoretical model of expenditures for a typical Canadian provincial government. The model is kept simple but useful by restricting the endogenous variables to four important budgetary categories: highway spending, hospital care expenditures, spending on schools and universities, and "all other" spending. Tax rates are also endogenous to the system. The choice of these four expenditure categories is linked to the original motivation for the model, which was to assist in explaining provincial construction spending. The theory has three elements: first, a utility function, which depends positively on the amounts provided of government services of various kinds, as well as on the income left to the public after taxes and borrowing; second, a budget constraint linking expenditures and revenues; and finally, a set of equations which show how much spending is required in order to provide the quantities of services entering as arguments into the utility function.The reduced form model developed from the theory is then fitted to expenditures data for each of the ten provinces over the 1952-1970 period. Fits are generally good. Tax equations, though not presented here, also fitted well. Provincial income levels, beginning year stocks of structures, rates of matching grants, construction prices and the closeness of elections are the main exogenous variables that prove important in explaining per capita expenditures within each of the four budgetary categories.